Controlling crosscut damage in response to excessive levels of horizontal stress: Case study at the Subtropolis Mine, Petersburg, OH - Nicole Evanek; Anthony Iannacchione; Tim Miller (Society for Mining, Metallurgy & Exploration)
The Subtropolis Mine is a room-and-pillar mine extracting the Vanport Limestone near Petersburg, OH. In February 2018, mine management began implementing a new mine layout to better control the negative effects of excessive levels of horizontal stress. Almost immediately, the conditions in the headings improved. Conversely, and as expected, stress-related damage was concentrated within crosscuts. Over the last 18 months, the mine operator has diligently experimented with different techniques/methods to lessen the impact of the instabilities in the outby crosscuts. The range of controls used by the mine operator include angled crosscuts, crosscut offsets, increased distance between crosscuts, arched crosscuts, cable-bolted crosscuts, altered blasting pattern, and windows. A window is used to resist roof deformation by leaving a strong brow of roof rock within the crosscuts.